Pengaruh Tugas Pokok Dan Fungsi Terhadap Kinerja Pegawai Negeri Sipil Pada Sekretariat Daerah Kabupaten Kepulauan Mentawai - Zalukhu, Mapyanis; Aromatica, Desna; Fatimah, Fatia (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2023)
This research which aims to determine the effect of the main tasks and functions on the performance of Civil Servants at the Regional Secretariat of the Mentawai Islands Regency is motivated by the existence of complaints and public dissatisfaction with the service that is not good and factual, there are still civil servants who do not understand the main tasks and functions, employee performance is still classified as not good, there are still employees who lack mastery of their work, there are many employees who carry out indirect work once so, so that the time required is longer and does not match the existing time standards, and there are still employees who have not carried out work duties in accordance with the objectives set at the Regional Secretariat of the Mentawai Islands District. This type of research uses a quantitative approach with multiple linear regression method. Data collection techniques with questionnaires. The respondents of this study were 90 Civil Servants at the Regional Secretariat of the Mentawai Islands District. The sampling method used the total sampling method where the entire population in this study was used as the research sample. Hypothesis testing is calculated with the IBM Statistical Package for Social Science (SPSS) version 24.0 program. From the results of this study it was found that partially the main tasks have a significant effect on performance, functions have a significant effect on performance, and simultaneously the main tasks and functions have a significant effect on the performance of Civil Servants at the Regional Secretariat of the Mentawai Islands District.